(untitled) (International Journal of Engineering and Computer Science, 2015)
Multimedia contains enormous amount of files it consumes more memory space, hard disk, energy and time. To overcome these problems we propose ―Robust information driven data compression architectures for wireless networks. The relationship between the values of sensors will be useful to improve the compression performance. In this, we are using two types of techniques; they are ―logical mapping algorithm and state of the distributed data compression. The cluster-based and information-driven architecture (RIDA) uses two types of transforms, discrete cosine transform and discrete wavelet transform. This architecture will reduce up to 30% of energy, 80-95% of bandwidth can be saved, and we can find the missing nodes also.